Anti-blue light contact lens and preparation method thereof
Hydrogel contact lenses prepared by heat-induced polymerization use tetraaryl metaloporphyrin compounds containing olefinic acid ester as anti-blue light agents to solve the problem of preparation of complex and blue light absorbers in the prior art, achieving high efficiency, Stable anti-blue light effect.
Patent Information
- Application Number
- CN202310546437.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-05-15
AI Technical Summary
The existing anti-blue light contact lens preparation methods are complex and costly, or there is a risk of precipitation of blue light absorbers, and it is not able to effectively distinguish between beneficial and harmful blue light absorption.
Hydrogel contact lenses prepared by heat-induced polymerization by reaction monomers, crosslinking agents, initiators and anti-blue light agents. The anti-blue light agents include tetraaryl metaloporphyrin compounds containing olefinic acid ester, which have better Solubility, photothermal stability and high-energy short-wave blue light absorption characteristics.
The anti-blue light contact lenses are achieved with simple preparation process and good photothermal stability. The blue light absorber is polymerized with the raw materials of the hydrogel lens, reducing the risk of precipitation. The anti-blue light effect remains consistent after the lens is soaked in water or under alcohol solvents. High safety and stable under different temperatures and light conditions.
Smart Images

Figure CN116715800B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of contact lenses, and particularly relates to an anti-blue light contact lens and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, people's dependence on electronic products has gradually increased, especially mobile phones, tablet computers, monitors, etc. These products will produce high-energy short-wave blue light. Harmful blue light in the 385-445nm band can penetrate the cornea and lens and directly reach the macular area of the fundus, causing damage to the macular area at the end of the eyeball. Traditional anti-blue light lenses are mainly resin lenses. As people's acceptance of contact lenses increases, anti-blue light contact lenses are increasingly valued by researchers.
[0003] There are two main methods for preparing anti-blue light contact lenses. One is to use a coating method to attach a coating with an anti-blue light effect to the surface or inner layer of the contact lens. In patent CN104808355B, a first anti-blue light layer and a second anti-blue light layer are attached to the contact lens body material, so that the contact lens has an anti-blue light effect. However, the preparation process of this method is complicated and the cost is greatly increased. The other is to mix the blue light absorber with the raw material by doping to prepare the anti-blue light contact lens. Patent CN102382237B proposes to mix 3 parts of quinophthalone solvent yellow or fluorescent polycyclic solvent yellow with contact lens raw materials to prepare anti-blue light contact lenses. The disadvantage is that this method has the risk of precipitation of blue light absorbers and does not distinguish between the absorption of beneficial and harmful blue light.
[0004] Therefore, there is an urgent need to develop an anti-blue light contact lens with a simple preparation process, good photothermal stability, and good blue light absorption selectivity. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a blue light resistant contact lens and a preparation method thereof.
[0006] Technical solution: In order to solve the above technical problems, the present invention provides an anti-blue light contact lens, which is formed by thermally initiating polymerization of at least one reactive monomer, a cross-linking agent, an initiator and an anti-blue light agent; the anti-blue light agent includes a tetraaryl metal porphyrin compound IM containing an alkene ester or tetrakis[4-(substituted acryloyloxy)phenyl]metal porphyrin II-M,
[0007] The structures of the IM and II-M are as follows:
[0008]
[0009]
[0010] X1, X2, X3, and X4 in the IM are each independently selected from one of hydrogen, halogen, cyano, nitro, alkyl, haloalkyl, and alkylcarbonyl; the halogen is fluorine, chlorine, bromine, or iodine; the halo in the haloalkyl is fluoro, chloro, bromo, or iodo; R is selected from H or alkyl; n=1 or 2 or 3 or 4; M is selected from divalent metal elements such as zinc, magnesium, and copper;
[0011] R in II-M is selected from H, methyl, ethyl or propyl; M is selected from divalent metal elements such as zinc, magnesium, copper, etc.
[0012] Preferably, the anti-blue light contact lens comprises at least one reactive monomer, a cross-linking agent, a solvent, an initiator and an anti-blue light agent, which are polymerized by thermal initiation.
[0013] Among them, the anti-blue light contact lens, calculated by mass, has 100 parts of the reaction monomer, 0 to 30% of the mass of the solvent, 0.01% to 0.5% of the mass of the reaction monomer, 0.01% to 1.5% of the mass of the initiator, and 0.01 to 1.5% of the mass of the cross-linking agent.
[0014] Wherein, the reactive monomers include methacrylate monomers, and the methacrylate monomers are 1 to 100 parts.
[0015] Wherein, the reactive monomer further comprises one or more of amide monomers or silicone monomers, the amide monomer is 0 to 50 parts, and the silicone monomer is 0 to 55 parts.
[0016] Among them, the methacrylate monomer includes any one or more of hydroxyethyl methacrylate, glycidyl methacrylate, glyceryl methacrylate, hydroxybutyl methacrylate, hydroxypropyl methacrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, and isobornyl methacrylate; the amide monomer includes any one or more of N-vinyl pyrrolidone, N,N-dimethylacrylamide, and N-methyl-N-vinylacetamide; the silicone monomer includes any one or more of 3-(3-methacryloyloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methylsilane, 3-acrylamidopropyltris(trimethylsiloxy)silane, monomethacrylamideoxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, methacryloxypropyltris(trimethylsiloxy)silane, monomethacryloxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, and fluorinated silicone methacrylate.
[0017] Among them, the anti-blue light contact lens, the initiator includes any one or two of azobisisobutyronitrile, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, bis(2-phenylethoxy) peroxydicarbonate, benzoyl peroxide, and azobisisoheptylnitrile, and the cross-linking agent includes any one or more of divinyl polyethylene glycol ester, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, triallyl isocyanurate, diethylene glycol divinyl ether, polyethylene glycol dimethacrylate, triethylene glycol diacrylate, and trimethylolpropane trimethacrylate.
[0018] Wherein, in the anti-blue light contact lens, the solvent includes any one or more of dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0019] The method for preparing the anti-blue light contact lens comprises the following steps: mixing the reaction monomer, initiator, cross-linking agent and anti-blue light agent in proportion, stirring, filtering, and dripping into the contact lens mold, thermally initiating polymerization and curing, hydrating with a hydrating liquid and then placing in standard saline to prepare the anti-blue light contact lens;
[0020] Alternatively, the reaction monomer, solvent, initiator, crosslinking agent and anti-blue light agent are mixed in proportion, stirred, filtered, and added dropwise to a contact lens mold, thermally initiated polymerization and cured, hydrated with a hydrating liquid, and then placed in standard saline to obtain an anti-blue light contact lens.
[0021] Among them, in the preparation method of the anti-blue light contact lens, the thermally initiated polymerization conditions are to react at a temperature of 60 to 130° C. for 1 to 40 hours in an inert gas atmosphere, and the inert gas includes any one of nitrogen, helium, and argon.
[0022] The hydration liquid includes pure water and any one of an aqueous solution of a surfactant or an aqueous solution of an organic solvent. The surfactant includes any one or two of poloxamer, polyether silicone oil, polyethylene glycol, and Tween. The organic solvent includes any one or two of ethanol, isopropanol, propylene glycol, glycerol, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide. The total hydration time of the aqueous solution of the surfactant or the aqueous solution of the organic matter and pure water is 2 to 12 hours. The mass fraction of the surfactant in the aqueous solution of the surfactant to water is 0.01% to 5%. The volume ratio of the organic solvent to water in the aqueous solution of the organic solvent is 10:90 to 90:10.
[0023] Specifically, the compound IM structural formula also includes:
[0024]
[0025]
[0026]
[0027] In the present invention, the preparation method of the tetraarylmetal porphyrin compound IM containing olefinic acid ester is as follows: Compound I and divalent metal acetate are stirred and reacted in a solvent to prepare compound IM, and the reaction formula is:
[0028]
[0029] Wherein, the divalent metal acetate is selected from zinc acetate, magnesium acetate or copper acetate, the molar ratio of the compound I to the divalent metal acetate is 1:1-20, the solvent is selected from dichloromethane, chloroform, N,N-dimethylformamide or N,N-dimethylacetamide, the stirring reaction temperature is 10°C-150°C, and the product needs to be separated and purified by column chromatography.
[0030] The preparation method of tetrakis[4-(substituted acryloyloxy)phenyl]metalloporphyrin II-M comprises the following steps: using tetrakis[(4-hydroxy)phenyl]porphyrin and alkyl-substituted acrylic acid as raw materials, preparing compound II through DCC (dicyclohexylcarbodiimide) condensation and DMAP (4-dimethylaminopyridine) catalysis, and then adding divalent metal acetate to react in a solvent with stirring to obtain compound II-M.
[0031]
[0032] Preferably, the alkyl-substituted acrylic acid includes methacrylic acid, ethacrylic acid or propylacrylic acid.
[0033] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0034] 1. The tetraarylmetal porphyrin containing olefin ester provided by the present invention has better solubility, photothermal stability and high-energy short-wave blue light absorption characteristics compared with the structure without metal, with the maximum absorption wavelength near 425nm and a wider absorption spectrum.
[0035] 2. The blue light absorber in the anti-blue light contact lens of the present invention has a double bond and can be polymerized with the hydrogel lens raw material, reducing the risk of precipitation of the blue light absorber. The prepared anti-blue light hydrogel lens is immersed in water or alcohol solvents, and the anti-blue light effect of the lens before and after immersion remains consistent, with high safety.
[0036] 3. The present invention adds solvents to the anti-blue light contact lens formula to improve the solubility of the anti-blue light agent; and the added solvents are all of high boiling point, which can avoid pollution caused by the vaporization of the solvent during the thermally initiated polymerization process; adding a surfactant or an aqueous solution of an organic solvent during the hydration process can more effectively soak out the unreacted anti-blue light agent and solvent, thereby improving the stability of the anti-blue light agent and shortening the hydration time.
[0037] 4. The anti-blue light contact lenses of the present invention have good photothermal stability. The lenses stored in standard saline are irradiated under sunlight for 36 hours, and the anti-blue light effect of the lenses does not change significantly. The anti-blue light effect of the lenses does not change before and after storage at 25°C and 45°C for 9 months, and the transmittance of the lenses at harmful blue light of 385-445nm remains almost unchanged.
[0038] 5. The anti-blue light contact lens of the present invention is a hydrogel contact lens. It is different from the traditional anti-blue light resin lens. The traditional anti-blue light resin lens only needs to be placed in a dry environment, and does not need to be stored in pure water or standard saline. Most resin lenses use the mechanism of blue light reflection to achieve the anti-blue light effect. The anti-blue light hydrogel lens needs to be placed in standard saline during transportation and storage, so the stability of the anti-blue light effect of the anti-blue light hydrogel lens in standard saline at different temperatures is particularly important. And the anti-blue light hydrogel lens achieves the effect of reducing the harm of blue light by absorbing harmful blue light. In other words, it absorbs the light energy of the harmful blue light band. The blue light absorber is prone to degradation after absorbing the light energy, so the light stability of the anti-blue light hydrogel contact lens is also very important. The anti-blue light hydrogel lens prepared by the present invention has good photothermal stability and stability in standard saline. Under strong sunlight, the anti-blue light effect remains stable; after being stored in standard saline at 25°C and 45°C for 9 months, the anti-blue light effect of the lens will not change. The spectral transmittance of the lens in the harmful blue light band of 385-445nm can be less than 80%, and the spectral transmittance in the beneficial blue light band of 446-505nm can be higher than 90%; more preferably, the spectral transmittance in the harmful blue light band of 385-445nm can be less than 10%, and the spectral transmittance in the beneficial blue light band of 446-505nm can be higher than 70%. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Hydrogen spectrum of compound I-1-Zn in Example 1.
[0040] Figure 2 Hydrogen spectrum of compound I-2-Cu in Example 2.
[0041] Figure 3 This is the anti-blue light hydrogel contact lens prepared in Example 32.
[0042] Figure 4This is the anti-blue light hydrogel contact lens prepared in Example 35.
[0043] Figure 5 It is a graph of the in vitro cell proliferation rate of Example 34 and Comparative Example 9. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below through specific examples.
[0045] Example 1 Synthesis of tetrakis[(4-butenoyloxy)phenyl]porphyrin zinc (Compound I-1-Zn)
[0046] Synthesis route of tetrakis[(4-butenoyloxy)phenyl]porphyrin zinc (compound I-1-Zn):
[0047]
[0048] Dissolve 0.95g of compound I-1 (synthesis method of invention patent CN115215874A) in 10mL of dichloromethane, add 0.2g of zinc acetate, and stir overnight at 25°C. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain the product I-1-Zn. NMR data ( 1 HNMR, 400 MHz, internal standard TMS, solvent CDCl3) is as follows: δ ppm 8.88 (d, J = 7.2 Hz, 8H), 8.22 (d, J = 8.4 Hz, 8H), 7.51 (d, J = 8.4 Hz, 8H), 6.25-6.12 (m, 4H), 5.44-5.36 (m, 8H), 3.55 (d, J = 6.8 Hz, 8H). (See hydrogen spectrum for details) Figure 1 )
[0049] Example 2 Synthesis of tetrakis[(4-butenoyloxy)phenyl]porphyrin copper (Compound I-1-Cu)
[0050] Synthesis route of tetrakis[(4-butenoyloxy)phenyl]porphyrin copper (Compound I-1-Cu):
[0051]
[0052] Dissolve 1.0 g of compound I-1 in 20 mL of chloroform, add 3.0 g of copper acetate, and stir at 60°C overnight. Remove the solvent by rotary evaporation, and separate and purify the product I-1-Cu by column chromatography. The elemental analysis data are as follows: calculated value w(C) = 71.17%, w(H) = 4.38%, w(N) = 5.53%; experimental value w(C) = 71.49%, w(H) = 4.36%, w(N) = 5.50%.
[0053] Example 3 Synthesis of tetrakis[(4-pentenoyloxy)phenyl]porphyrin copper (Compound I-2-Cu)
[0054] Synthesis route of tetrakis[(4-pentenoyloxy)phenyl]porphyrin copper (Compound I-2):
[0055]
[0056] First, refer to the synthesis method of compound I-2 in invention patent CN115215874A to prepare tetrakis[(4-pentenoyloxy)phenyl]porphyrin (compound I-2). Dissolve 1.01g of compound I-2 in 20mL of chloroform, add 1.8g of copper acetate, and stir at 60°C overnight. Remove the solvent by rotary evaporation, and separate and purify the product I-2-Cu by column chromatography. NMR data ( 1 H NMR, 400 MHz, internal standard TMS, solvent CDCl3) are as follows: 8.93 (d, J = 7.2 Hz, 8H), 8.25 (d, J = 8.4 Hz, 8H), 7.32 (d, J = 8.4 Hz, 8H), 6.05 (m, 4H), 5.25 (m, 8H), 2.75 (t, J = 7.2 Hz, 8H), 2.62 (t, J = 7.2 Hz, 8H). (See hydrogen spectrum for details) Figure 2 )
[0057] Example 4 Synthesis of tetrakis[(4-hexenoyloxy)phenyl]porphyrin zinc (Compound I-3-Zn)
[0058] Synthesis route of tetrakis[(4-hexenoyloxy)phenyl]porphyrin zinc (compound I-3-Zn):
[0059]
[0060] First, tetrakis[(4-hexenoyloxy)phenyl]porphyrin (Compound I-3) was prepared by referring to the synthesis method of Compound I-3 of invention patent CN115215874A. 1.06g of Compound I-3 was dissolved in 10mL of chloroform, 0.4g of zinc acetate was added, and stirred overnight at 20°C. The solvent was removed by rotary evaporation, and the product I-3-Zn was separated and purified by column chromatography. The elemental analysis data are as follows: calculated value w(C) = 72.49%, w(H) = 5.37%, w(N) = 4.97%; experimental value w(C) = 72.78%, w(H) = 5.40%, w(N) = 4.95%.
[0061] Example 5 Synthesis of tetrakis[(4-hexenoyloxy)phenyl]porphyrin copper (Compound I-3-Cu)
[0062] Synthesis route of tetrakis[(4-hexenoyloxy)phenyl]porphyrin copper (compound I-3-Cu):
[0063]
[0064] 1.06 g of compound I-3 was dissolved in 20 mL of chloroform, 3.0 g of copper acetate was added, and the mixture was stirred at 60°C overnight. The solvent was removed by rotary evaporation, and the product I-3-Cu was separated and purified by column chromatography. The elemental analysis data are as follows: calculated values w(C) = 72.61%, w(H) = 5.38%, w(N) = 4.98%; experimental values w(C) = 72.92%, w(H) = 5.35%, w(N) = 4.96%.
[0065] Example 6 Synthesis of tetrakis[(4-methylbutenoyloxy)phenyl]porphyrin copper (Compound I-4-Cu)
[0066] Synthesis route of tetrakis[(4-methylbutenoyloxy)phenyl]porphyrin copper (compound I-4-Cu):
[0067]
[0068] First, refer to the synthesis method of compound I-4 of invention patent CN115215874A to prepare tetrakis[(4-methylbutylene oxy)phenyl]porphyrin (compound I-4). Dissolve 1.01g of compound I-4 in 20mL of chloroform, add 1.5g of copper acetate, and stir at 60°C overnight. Remove the solvent by rotary evaporation, and separate and purify the product I-4-Cu by column chromatography. The elemental analysis data are as follows: calculated value w(C)=71.93%, w(H)=4.90%, w(N)=5.24%; experimental value w(C)=72.22%, w(H)=4.87%, w(N)=5.21%.
[0069] Example 7 Synthesis of tetrakis[(4-methylpentenoyloxy)phenyl]porphyrin magnesium (Compound I-5-Mg)
[0070] Synthesis route of tetrakis[(4-methylpentenoyloxy)phenyl]porphyrin magnesium (Compound I-5-Mg):
[0071]
[0072] First, refer to the synthesis method of compound I-5 of invention patent CN115215874A to prepare tetrakis[(4-methylpentenoyloxy)phenyl]porphyrin (compound I-5). Dissolve 0.53g of compound I-5 in 10mL DMF, add 0.71g of magnesium acetate, and stir overnight at 150°C. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I-5-Mg. The elemental analysis data are as follows: calculated value w(C)=75.24%, w(H)=5.57%, w(N)=5.16%; experimental value w(C)=74.95%, w(H)=5.59%, w(N)=5.18%.
[0073] Example 8 Synthesis of tetrakis[(4-methylhexenoyloxy)phenyl]porphyrin zinc (Compound I-6-Zn)
[0074] Synthesis route of tetrakis[(4-methylhexenoyloxy)phenyl]porphyrin zinc (compound I-6-Zn):
[0075]
[0076] First, refer to the synthesis method of compound I-6 in invention patent CN115215874A to prepare tetrakis[(4-methylhexenoyloxy)phenyl]porphyrin (compound I-6). Dissolve 1.12g of compound I-6 in 10mL of dichloromethane, add 0.92g of zinc acetate, and stir overnight at 10°C. Remove the solvent by rotary evaporation, and separate and purify the product I-6-Zn by column chromatography. The elemental analysis data are as follows: calculated value w(C)=73.12%, w(H)=5.80%, w(N)=4.74%; experimental value w(C)=73.42%, w(H)=5.77%, w(N)=4.72%.
[0077] Example 9 Synthesis of tetrakis[(4-ethylbutenoyloxy)phenyl]porphyrin magnesium (Compound I-7-Mg)
[0078] Synthesis route of tetrakis[(4-ethylbutenoyloxy)phenyl]porphyrin magnesium (compound I-7-Mg):
[0079]
[0080] First, refer to the synthesis method of compound I-7 in invention patent CN115215874A to prepare tetrakis[(4-ethylbutenoyloxy)phenyl]porphyrin (compound I-7). Dissolve 1.06g of compound I-7 in 10mLN,N-dimethylacetamide, add 0.55g of magnesium acetate, and stir overnight at 120°C. Remove the solvent by rotary evaporation, and separate and purify the product I-7-Mg by column chromatography. The elemental analysis data are as follows: calculated value w(C)=75.24%, w(H)=5.57%, w(N)=5.16%; experimental value w(C)=74.95%, w(H)=5.59%, w(N)=5.18%.
[0081] Example 10 Synthesis of tetrakis[(4-ethylpentenoyloxy)phenyl]porphyrin copper (Compound I-8-Cu)
[0082] Synthesis route of tetrakis[(4-ethylpentenoyloxy)phenyl]porphyrin copper (compound I-8-Cu):
[0083]
[0084] First, refer to the synthesis method of compound I-8 in invention patent CN115215874A to prepare tetrakis[(4-ethylpentenoyloxy)phenyl]porphyrin (compound I-8). Dissolve 1.12g of compound I-8 in 20mL of chloroform, add 2.0g of copper acetate, and stir overnight at 40°C. Remove the solvent by rotary evaporation, and separate and purify the product I-8-Cu by column chromatography. The elemental analysis data are as follows: calculated value w(C)=73.23%, w(H)=5.80%, w(N)=4.74%; experimental value w(C)=73.55%, w(H)=5.77%, w(N)=4.72%.
[0085] Example 11 Synthesis of tetrakis[(4-chloro-3-butenoyloxy)phenyl]porphyrin copper (Compound I-9-Cu)
[0086] Synthesis route of tetrakis[(4-chloro-3-butenoyloxy)phenyl]porphyrin copper (compound I-9-Cu)
[0087]
[0088] First, refer to the synthesis method of compound I-9 in invention patent CN115215874A to prepare tetrakis[(4-chloro-3-butenoyloxy)phenyl]porphyrin copper (compound I-9). Dissolve 1.09g of compound I-9 in 20mLN,N-dimethylacetamide, add 1.5g of copper acetate, and stir overnight at 40°C. Remove the solvent by rotary evaporation, and separate and purify the product I-9-Cu by column chromatography. The elemental analysis data are as follows: calculated value w(C)=62.65%, w(H)=3.51%, w(N)=4.87%; experimental value w(C)=62.36%, w(H)=3.53%, w(N)=4.89%.
[0089] Example 12 Synthesis of tetrakis[(2-chloro-4-pentenoyloxy)phenyl]porphyrin copper (Compound I-10-Cu)
[0090] Synthesis route of tetrakis[(2-chloro-4-pentenoyloxy)phenyl]porphyrin copper (compound I-10-Cu):
[0091]
[0092] First, refer to the synthesis method of compound I-10 of invention patent CN115215874A to prepare tetrakis[(2-chloro-4-pentenoyloxy)phenyl]porphyrin (compound I-10). Dissolve 1.14g of compound I-10 in 30mL of dichloromethane, add 1.2g of copper acetate, and stir at 35°C overnight. Remove the solvent by rotary evaporation, and separate and purify the product I-10-Cu by column chromatography. The elemental analysis data are as follows: calculated value w(C)=63.72%, w(H)=4.01%, w(N)=4.64%; experimental value w(C)=63.42%, w(H)=4.03%, w(N)=4.67%.
[0093] Example 13 Synthesis of tetrakis[(3-cyano-4-butenoyloxy)phenyl]porphyrin zinc (Compound I-11-Zn)
[0094] Synthesis route of tetrakis[(3-cyano-4-butenoyloxy)phenyl]porphyrin zinc (compound I-11-Zn):
[0095]
[0096] First, refer to the synthesis method of compound I-11 in invention patent CN115215874A to prepare tetra[(3-cyano-4-butenoyloxy)phenyl]porphyrin (compound I-11). Dissolve 1.05g of compound I-11 in 30mL of dichloromethane, add 1.1g of zinc acetate, and stir overnight at 25°C. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I-11-Zn. Elemental analysis data are as follows: calculated value w(C) = 68.98%, w(H) = 3.62%, w(N) = 10.05%; experimental value w(C) = 69.29%, w(H) = 3.60%, w(N) = 10.01%.
[0097] Example 14 Synthesis of tetrakis[(3-nitro-4-pentenoyloxy)phenyl]porphyrin magnesium (Compound I-12-Mg)
[0098] Synthesis route of tetrakis[(3-nitro-4-pentenoyloxy)phenyl]porphyrin magnesium (compound I-12-Mg):
[0099]
[0100] First, refer to the synthesis method of compound I-12 in invention patent CN115215874A to prepare tetrakis[(3-nitro-4-pentenoyloxy)phenyl]porphyrin (compound I-12). Dissolve 1.19g of compound I-12 in 10mLN,N-dimethylformamide, add 0.8g of magnesium acetate, and stir overnight at 110°C. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I-12-Mg. The elemental analysis data are as follows: calculated value w(C)=63.56%, w(H)=4.00%, w(N)=9.27%; experimental value w(C)=63.88%, w(H)=3.98%, w(N)=9.22%.
[0101] Example 15 Synthesis of tetrakis[(2-methyl-4-methylbutenoyloxy)phenyl]porphyrin copper (Compound I-13-Cu)
[0102] Synthesis route of tetrakis[(2-methyl-4-methylbutenoyloxy)phenyl]porphyrin copper (compound I-13-Cu):
[0103]
[0104] First, refer to the synthesis method of compound I-13 of invention patent CN115215874A to prepare tetrakis[(2-methyl-4-methylbutenoyloxy)phenyl]porphyrin (compound I-13). Dissolve 1.06g of compound I-13 in 30mL of dichloromethane, add 2.0g of copper acetate, and stir at 30°C overnight. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I-I3-Cu. The elemental analysis data are as follows: calculated value w(C)=72.61%, w(H)=5.38%, w(N)=4.98%; experimental value w(C)=72.90%, w(H)=5.35%, w(N)=4.96%.
[0105] Example 16 Synthesis of tetrakis[(3-ethyl-4-methylpentenoyloxy)phenyl]porphyrin zinc (Compound I-14-Zn)
[0106] Synthesis route of tetrakis[(3-ethyl-4-methylpentenoyloxy)phenyl]porphyrin zinc (compound I-14-Zn):
[0107]
[0108] First, refer to the synthesis method of compound I-14 of invention patent CN115215874A to prepare tetrakis[(3-ethyl-4-methylpentenoyloxy)phenyl]porphyrin (compound I-14). Dissolve 1.18g of compound I-14 in 30mL of chloroform, add 1.2g of zinc acetate, and stir overnight at 40°C. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I-I4-Zn. Elemental analysis data are as follows: calculated value w(C)=73.68%, w(H)=6.18%, w(N)=4.52%; experimental value w(C)=73.92%, w(H)=6.15%, w(N)=4.50%.
[0109] Example 17 Synthesis of tetrakis[(3-trifluoromethyl-4-butenoyloxy)phenyl]porphyrin copper (Compound I-15-Cu)
[0110] Synthesis route of tetrakis[(3-trifluoromethyl-4-butenoyloxy)phenyl]porphyrin copper (compound I-15-Cu):
[0111]
[0112] First, refer to the synthesis method of compound I-15 of invention patent CN115215874A to prepare tetrakis[(3-trifluoromethyl-4-butenoyloxy)phenyl]porphyrin (compound I-15). Dissolve 1.22g of compound I-15 in 30mL of chloroform, add 2.5g of copper acetate, and stir at 60°C overnight. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I-15-Cu. Elemental analysis data are as follows: calculated value w(C) = 59.84%, w(H) = 3.14%, w(N) = 4.36%; experimental value w(C) = 59.55%, w(H) = 3.16%, w(N) = 4.39%.
[0113] Example 18 Synthesis of tetrakis[(2,4-dichloro-5-butenoyloxy)phenyl]porphyrin magnesium (Compound I-16-Mg)
[0114] Synthesis route of tetrakis[(2,4-dichloro-5-butenoyloxy)phenyl]porphyrin magnesium (compound I-16-Mg):
[0115]
[0116] First, refer to the synthesis method of compound I-16 in invention patent CN115215874A to prepare tetrakis[(2,4-dichloro-5-butenoyloxy)phenyl]porphyrin (compound I-16). Dissolve 1.22g of compound I-16 in 15mLN,N-dimethylformamide, add 1.2g of magnesium acetate, and stir at 150°C overnight. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I-16-Mg. Elemental analysis data are as follows: calculated value w(C)=57.70%, w(H)=2.91%, w(N)=4.49%; experimental value w(C)=57.39%, w(H)=2.93%, w(N)=4.52%.
[0117] Example 19 Synthesis of tetrakis[(3-isopropyl-5-methylbutenoyloxy)phenyl]porphyrin zinc (Compound I-17-Zn)
[0118] Synthesis route of tetrakis[(3-isopropyl-5-methylbutenoyloxy)phenyl]porphyrin zinc (compound I-17-Zn):
[0119]
[0120] First, refer to the synthesis method of compound I-17 in invention patent CN115215874A to prepare tetrakis[(3-isopropyl-5-methylbutenoyloxy)phenyl]porphyrin (compound I-17). Dissolve 1.17g of compound I-17 in 30mL of chloroform, add 1.5g of zinc acetate, and stir at 30°C overnight. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain the product I-17-Zn. The elemental analysis data are as follows: calculated value w(C)=73.76%, w(H)=6.35%, w(N)=4.47%; experimental value w(C)=73.43%, w(H)=6.38%, w(N)=4.49%.
[0121] Example 20 Synthesis of tetrakis[(4-fluoro-3-pentenoyloxy)phenyl]porphyrin magnesium (Compound I-18-Mg)
[0122] Synthesis route of tetrakis[(4-fluoro-3-pentenoyloxy)phenyl]porphyrin magnesium (compound I-18-Mg):
[0123]
[0124] First, refer to the synthesis method of compound I-18 of invention patent CN115215874A to prepare tetrakis[(4-fluoro-3-pentenoyloxy)phenyl]porphyrin (compound I-18). Dissolve 1.08g of compound I-18 in 15mL N,N-dimethylacetamide, add 1.8g of magnesium acetate, and stir overnight at 140°C. Remove the solvent by rotary evaporation, and separate and purify the product I-18-Mg by column chromatography. The elemental analysis data are as follows: calculated value w(C)=69.79%, w(H)=4.39%, w(N)=5.09%; experimental value w(C)=67.11%, w(H)=4.37%, w(N)=5.06%.
[0125] Example 21 Synthesis of tetrakis[4-(methacryloyloxy)phenyl]porphyrin zinc (Compound II-1-Zn)
[0126]
[0127] First, refer to the synthesis method of compound I-1 in invention patent CN115215874A, use tetrakis[(4-hydroxy)phenyl]porphyrin and methacrylic acid as raw materials, condense with DCC (dicyclohexylcarbodiimide) and catalyze with DMAP (4-dimethylaminopyridine) to prepare tetrakis[4-(methacryloyloxy)phenyl]porphyrin (compound II-1). Dissolve 0.95g of compound II-1 in 30mL of dichloromethane, add 1.8g of zinc acetate, and stir at 30°C overnight. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product II-1-Zn. NMR data ( 1 H NMR, 400 MHz, internal standard TMS, solvent DMSO-d6) is as follows: δ ppm 8.92 (s, 8H), 8.25 (d, J = 8.2 Hz, 8H), 7.56 (d, J = 8.2 Hz, 8H), 6.56 (s, 4H), 5.92 (s, 4H), 2.23 (s, 12H).
[0128] Example 22 Synthesis of tetrakis[4-(methacryloyloxy)phenyl]porphyrin copper (Compound II-1-Cu)
[0129]
[0130] Dissolve 1.0 g of compound II-1 in 30 mL of chloroform, add 2.7 g of copper acetate, and stir at 60°C overnight. Remove the solvent by rotary evaporation, and separate and purify the product II-1-Cu by column chromatography. The elemental analysis data are as follows: calculated value w(C) = 71.17%, w(H) = 4.38%, w(N) = 5.53%; experimental value w(C) = 78.82%, w(H) = 4.40%, w(N) = 5.56%.
[0131] Example 23 Synthesis of tetrakis[4-(methacryloyloxy)phenyl]porphyrin magnesium (Compound II-1-Mg)
[0132]
[0133] Dissolve 0.95g of compound II-1 in 15mL N,N-dimethylformamide, add 1.6g of magnesium acetate, and stir at 150°C overnight. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product II-1-Mg. NMR data ( 1 H NMR, 400 MHz, internal standard TMS, solvent DMSO-d6) is as follows: δ ppm 8.95 (s, 8H), 8.24 (d, J=8.2 Hz, 8H), 7.43 (d, J=8.2 Hz, 8H), 6.42 (s, 4H), 5.86 (s, 4H), 2.18 (s, 12H).
[0134] Example 24 Synthesis of tetrakis[4-(ethylacryloyloxy)phenyl]porphyrin copper (Compound II-2-Zn)
[0135]
[0136] First, refer to the synthesis method of compound I-1 of invention patent CN115215874A, and use tetrakis[(4-hydroxy)phenyl]porphyrin and ethyl acrylic acid as raw materials, and prepare tetrakis[4-(ethylacryloyloxy)phenyl]porphyrin (compound II-2) by DCC condensation and DMAP catalysis. Dissolve 1.05g of compound II-2 in 30mL of dichloromethane, add 1.5g of zinc acetate, and stir overnight at 20°C. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product II-2-Zn. Elemental analysis data are as follows: calculated value w(C)=71.81%, w(H)=4.90%, w(N)=5.23%; experimental value w(C)=71.49%, w(H)=4.92%, w(N)=5.26%.
[0137] Example 25 Synthesis of tetrakis[4-(propylacryloyloxy)phenyl]porphyrin copper (Compound II-3-Cu)
[0138]
[0139] First, refer to the synthesis method of compound I-1 of invention patent CN115215874A, and use tetrakis[(4-hydroxy)phenyl]porphyrin and propyl acrylic acid as raw materials, and prepare tetrakis[4-(propylacryloyloxy)phenyl]porphyrin (compound II-3) by DCC condensation and DMAP catalysis. Dissolve 1.0g of compound II-3 in 10mLN,N-dimethylformamide, add 2.5g of copper acetate, and stir at 60°C overnight. Remove the solvent by rotary evaporation, and separate and purify by column chromatography to obtain product I1-3-Cu. Elemental analysis data are as follows: calculated value w(C)=72.51%, w(H)=5.18%, w(N)=5.05%; experimental value w(C)=72.82%, w(H)=5.15%, w(N)=5.02%.
[0140] Example 26 Preparation of Anti-Blue Light Hydrogel Lenses
[0141] 50g of hydroxyethyl methacrylate (HEMA), 0.075g of anti-blue light agent (compound I-1-Zn), 0.25g of azobisisobutyronitrile and 0.25g of ethylene glycol dimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 75°C for 12h under a nitrogen atmosphere, demolded after the reaction, placed in a propylene glycol aqueous solution with a volume ratio of 10:90 for hydration for 0.5h, hydrated in pure water for 1.5h, and then transferred to standard saline to prepare an anti-blue light hydrogel contact lens.
[0142] Comparative Example 1 Preparation of hydrogel lenses
[0143] 50g of hydroxyethyl methacrylate (HEMA), 0.25g of azobisisobutyronitrile and 0.25g of ethylene glycol dimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped dropwise into a mold, reacted at 75°C for 12h under a nitrogen atmosphere, demolded after the reaction, placed in a propylene glycol aqueous solution with a volume ratio of 10:90 for hydration for 0.5h, hydrated in pure water for 1.5h, and then transferred to standard saline to prepare a hydrogel contact lens.
[0144] Example 27 Preparation of Anti-Blue Light Hydrogel Lenses
[0145] 44g of hydroxyethyl methacrylate (HEMA), 4g of glycidyl methacrylate, 2g of hydroxybutyl methacrylate, 0.005g of an anti-blue light agent (compound I-2-Cu), 0.005g of benzoyl peroxide and 0.20g of triethylene glycol dimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 60°C for 40h under a helium atmosphere, demolded after the reaction, placed in a dimethyl sulfoxide aqueous solution with a volume ratio of 50:50 for hydration for 1h, hydrated in pure water for 5h, and finally transferred into standard saline to obtain an anti-blue light hydrogel contact lens.
[0146] Comparative Example 2 Preparation of hydrogel lenses
[0147] 44g of hydroxyethyl methacrylate (HEMA), 4g of glycidyl methacrylate, 2g of hydroxybutyl methacrylate, 0.005g of benzoyl peroxide and 0.20g of triethylene glycol dimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 60°C for 40h under a helium atmosphere, demolded after the reaction, placed in a dimethyl sulfoxide aqueous solution with a volume ratio of 50:50 for hydration for 1h, hydrated in pure water for 5h, and finally transferred into standard saline to prepare a hydrogel contact lens.
[0148] Example 28 Preparation of Anti-Blue Light Hydrogel Lenses
[0149] 36g of hydroxyethyl methacrylate, 3g of hydroxypropyl methacrylate, 6g of N-vinyl pyrrolidone, 5g of N-methyl-N-vinylacetamide, 0.015g of anti-blue light agent (compound I-5-Mg), 0.05g of azobisisoheptanenitrile, 0.1g of ethylene glycol dimethacrylate, and 0.1g of diethylene glycol divinyl ether were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold dropwise, reacted at 130°C under an argon atmosphere for 5h. After the reaction, the mold was removed, placed in a 1% Tween 80 aqueous solution for hydration for 1h, hydrated in pure water for 3h, and then transferred to standard saline to obtain an anti-blue light hydrogel contact lens.
[0150] Comparative Example 3 Preparation of hydrogel lenses
[0151] 36g of hydroxyethyl methacrylate, 3g of hydroxypropyl methacrylate, 6g of N-vinyl pyrrolidone, 5g of N-methyl-N-vinylacetamide, 0.005g of azobisisoheptanenitrile, 0.1g of ethylene glycol dimethacrylate, and 0.1g of diethylene glycol divinyl ether were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold dropwise, reacted at 130°C for 5h under an argon atmosphere, demolded after the reaction, placed in a 1% Tween 80 aqueous solution for hydration for 1h, hydrated in pure water for 3h, and then transferred to standard saline to prepare a hydrogel contact lens.
[0152] Example 29 Preparation of Anti-Blue Light Hydrogel Lenses
[0153] 30g of methyl methacrylate, 8g of ethyl methacrylate, 12g of N-vinylpyrrolidone, 0.02g of anti-blue light agent (compound I-1-Zn), 0.3g of azobisisobutyronitrile and 0.32g of trimethylolpropane trimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 110°C for 12h under a nitrogen atmosphere, demolded after the reaction, placed in an ethanol-water solution with a volume ratio of 20:80 for hydration for 3h, then transferred to pure water for hydration for 9h, and finally transferred to standard saline to obtain an anti-blue light hydrogel contact lens.
[0154] Comparative Example 4 Preparation of hydrogel lenses
[0155] 30g of methyl methacrylate, 8g of ethyl methacrylate, 12g of N-vinyl pyrrolidone, 0.02g of anti-blue light agent (compound I-1-Zn), 0.3g of azobisisobutyronitrile and 0.32g of trimethylolpropane trimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 110°C for 12h under a nitrogen atmosphere, demolded after the reaction, placed in an ethanol-water solution with a volume ratio of 20:80 for hydration for 3h, then transferred to pure water for hydration for 9h, and finally transferred to standard saline to obtain a hydrogel contact lens.
[0156] Example 30 Preparation of Anti-blue Light Hydrogel Lenses
[0157] 43g of hydroxyethyl methacrylate (HEMA), 3g of butyl methacrylate, 4g of methacrylic acid, 0.025g of an anti-blue light agent (compound I-2-Cu), 0.25g of benzoyl peroxide and 0.75g of polyethylene glycol dimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 130°C for 1h under a nitrogen atmosphere, demolded after the reaction, hydrated in an N,N-dimethylformamide aqueous solution with a volume ratio of 10:90 for 3h, placed in pure water for hydration for 3h, and then transferred to standard saline to prepare an anti-blue light hydrogel contact lens.
[0158] Comparative Example 5 Preparation of hydrogel lenses
[0159] 43g of hydroxyethyl methacrylate (HEMA), 3g of butyl methacrylate, 4g of methacrylic acid, 0.25g of benzoyl peroxide and 0.75g of polyethylene glycol dimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped dropwise into a mold, reacted at 130°C for 1h under a nitrogen atmosphere, demolded after the reaction, hydrated in an N,N-dimethylformamide aqueous solution with a volume ratio of 10:90 for 3h, placed in pure water for hydration for 3h, and then transferred to standard saline to prepare a hydrogel contact lens.
[0160] Example 31 Preparation of blue light resistant silicone hydrogel lenses
[0161] 3g of hydroxyethyl methacrylate, 17g of 3-(3-methacryloyloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methylsilane, 5g of propyl methacrylate, 25g of N,N-dimethylacrylamide, 0.05g of an anti-blue light agent (compound I-7-Mg), 0.25g of diisopropyl peroxydicarbonate and 0.35g of triallyl isocyanurate were mixed and stirred at room temperature for 12h, filtered, and dripped into a mold dropwise, reacted at 80°C for 18h under a nitrogen atmosphere, demolded after the reaction, hydrated in an isopropanol aqueous solution with a volume ratio of 80:20 for 0.5h, then hydrated in an ethanol aqueous solution with a volume ratio of 50:50 for 0.5h, then transferred into pure water for hydration for 10h, and finally placed in standard saline to obtain an anti-blue light silicone hydrogel contact lens.
[0162] Comparative Example 6 Preparation of Silicone Hydrogel Lenses
[0163] 3g of hydroxyethyl methacrylate, 17g of 3-(3-methacryloyloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methylsilane, 5g of propyl methacrylate, 25g of N,N-dimethylacrylamide, 0.25g of diisopropyl peroxydicarbonate and 0.35g of triallyl isocyanurate were mixed and stirred at room temperature for 12h, filtered, and dripped into a mold drop by drop, reacted at 80°C for 18h under a nitrogen atmosphere, demolded after the reaction, hydrated in an isopropanol aqueous solution with a volume ratio of 80:20 for 0.5h, then hydrated in an ethanol aqueous solution with a volume ratio of 50:50 for 0.5h, then transferred into pure water for hydration for 10h, and finally placed in standard saline to prepare a silicone hydrogel contact lens.
[0164] Example 32 Preparation of Anti-Blue Light Silicone Hydrogel Lenses
[0165] 4g of mono-methacryloxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, 4g of 3-(3-methacryloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methylsilane, 7g of methyl methacrylate, 35g of hydroxyethyl methacrylate, 0.01g of anti-blue light agent (Compound I-12-Mg), 0.75g of benzoyl peroxide, and 0.75g of polyethylene glycol dimethacrylate were mixed and stirred at room temperature for 24 hours, filtered, and dripped into a mold dropwise, and reacted at 60°C for 22 hours under an argon atmosphere. After the reaction, the mold was demolded, placed in a mixed aqueous solution containing 1% poloxamer and 1% polyether silicone oil (DBE-821, Mn=4400, 80-85% ethylene oxide) for hydration for 5 hours, then placed in pure water for hydration for 6 hours, and finally placed in standard saline to obtain an anti-blue light silicone hydrogel contact lens.
[0166] Comparative Example 7 Preparation of Silicone Hydrogel Lenses
[0167] 4 g of mono-methacryloxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, 4 g of 3-(3-methacryloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methylsilane, 7 g of methyl methacrylate, 35 g of hydroxyethyl methacrylate, 0.75 g of benzoyl peroxide, and 0.75 g of polyethylene glycol dimethacrylate were mixed and stirred at room temperature for 24 hours, filtered, and dripped into a mold dropwise, reacted at 60° C. for 22 hours under an argon atmosphere, demolded after the reaction, placed in a mixed aqueous solution containing 1% poloxamer and 1% polyether silicone oil (DBE-821, Mn=4400, 80-85% ethylene oxide) for hydration for 5 hours, then placed in pure water for hydration for 6 hours, and finally placed in standard saline to prepare a silicone hydrogel contact lens.
[0168] Example 33 Preparation of Anti-blue Light Silicone Hydrogel Lenses
[0169] 15g 3-acrylamidopropyl tris(trimethylsiloxy)silane, 25g methacrylate glycerol, 10g N-methyl-N-vinylacetamide, 0.25g anti-blue light agent (Compound I-11-Zn), 0.5g dicyclohexyl peroxydicarbonate, 0.4g polyethylene glycol dimethacrylate, 5g N,N-dimethylformamide, 5g dimethyl sulfoxide, mixed and stirred at room temperature for 24h, filtered, dripped into the mold drop by drop, reacted at 75°C under argon atmosphere for 18h, demolded after the reaction, hydrated in an N,N-dimethylacetamide aqueous solution with a volume ratio of 30:70 for 3h, then transferred into pure water for hydration for 5h, and finally placed in standard saline to obtain an anti-blue light silicone hydrogel contact lens.
[0170] Comparative Example 8 Preparation of Silicone Hydrogel Lenses
[0171] 15g 3-acrylamidopropyl tris(trimethylsiloxy)silane, 25g methacrylate glycerol, 10g N-methyl-N-vinylacetamide, 0.5g dicyclohexyl peroxydicarbonate, 0.4g polyethylene glycol dimethacrylate, 5g N,N-dimethylformamide, and 5g dimethyl sulfoxide were mixed and stirred at room temperature for 24h, filtered, and dripped into a mold dropwise, reacted at 75°C for 18h under argon atmosphere, demolded after the reaction, hydrated in an N,N-dimethylacetamide aqueous solution with a volume ratio of 30:70 for 3h, then transferred into pure water for hydration for 5h, and finally placed in standard saline to obtain a silicone hydrogel contact lens.
[0172] Example 34 Preparation of Anti-blue Light Silicone Hydrogel Lenses
[0173] 18.5g 3-(3-methacryloyloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methyl silane, 6g methacryloyloxypropyltri(trimethylsiloxane)silane, 3g monomethylacrylamideoxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, 16g isobornyl methacrylate, 6.5g N-vinyl pyrrolidone, 5g N,N-dimethylformamide, 0.125g anti-blue light agent (compound I-14-Zn), 0.5g azobisisobutyronitrile, 0.005g diethylene glycol divinyl ether, mixed and stirred at room temperature for 24h, filtered, dripped into the mold drop by drop, reacted at 85°C under helium atmosphere for 16h, demolded after the reaction, hydrated in a glycerol aqueous solution with a volume ratio of 40:60 for 3h, then transferred into pure water for hydration for 5h, and finally placed in standard saline to obtain an anti-blue light silicone hydrogel contact lens.
[0174] Comparative Example 9 Preparation of Silicone Hydrogel Lenses
[0175] 18.5g 3-(3-methacryloyloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methylsilane, 6g methacryloyloxypropyltri(trimethylsiloxane)silane, 3g monomethacrylamideoxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, 16g isobornyl methacrylate, 6.5g N-vinyl pyrrolidone, 5g N,N-dimethylformamide, 0.5g azobisisobutyronitrile, 0.005g diethylene glycol divinyl ether, mixed and stirred at room temperature for 24h, filtered, dripped into the mold drop by drop, reacted at 85°C for 16h under helium atmosphere, demolded after the reaction, hydrated in a glycerol aqueous solution with a volume ratio of 40:60 for 3h, then transferred into pure water for hydration for 5h, and finally placed in standard saline to obtain an anti-blue light silicone hydrogel contact lens.
[0176] Example 35 Preparation of Anti-blue Light Silicone Hydrogel Lenses
[0177] 20g of methacryloxypropyl tris(trimethylsiloxy)silane, 5g of fluorinated siloxane methacrylate, 9g of methyl methacrylate, 16g of hydroxyethyl methacrylate, 0.06g of anti-blue light agent (Compound I-17-Zn), 0.5g of azobisisobutyronitrile, 0.25g of tetraethylene glycol dimethacrylate, 0.25g of diethylene glycol divinyl ether, 10g of N,N-dimethylacetamide, and 5g of N,N-dimethylformamide were mixed and stirred at room temperature for 24h, filtered, and dripped into the mold drop by drop, reacted at 100°C for 14h under a helium atmosphere, demolded after the reaction, hydrated in an N,N-dimethylacetamide aqueous solution with a volume ratio of 80:20 for 0.5h, then transferred into pure water for hydration for 10h, and finally placed in standard saline to obtain an anti-blue light silicone hydrogel contact lens.
[0178] Comparative Example 10 Preparation of Silicone Hydrogel Lenses
[0179] 20g of methacryloxypropyl tris(trimethylsiloxy)silane, 5g of fluorinated siloxane methacrylate, 9g of methyl methacrylate, 16g of hydroxyethyl methacrylate, 0.5g of azobisisobutyronitrile, 0.25g of tetraethylene glycol dimethacrylate, 0.25g of diethylene glycol divinyl ether, 10g of N,N-dimethylacetamide, and 5g of N,N-dimethylformamide were mixed and stirred at room temperature for 24h, filtered, and dripped into a mold drop by drop, reacted at 100°C for 14h under a helium atmosphere, demolded after the reaction, hydrated in an N,N-dimethylacetamide aqueous solution with a volume ratio of 80:20 for 0.5h, then transferred into pure water for hydration for 10h, and finally placed in standard saline to obtain a silicone hydrogel contact lens.
[0180] Example 36 Preparation of Anti-Blue Light Hydrogel Lenses
[0181] 40g of glyceryl methacrylate, 10g of N-vinyl pyrrolidone, 0.025g of anti-blue light agent (compound I-1-Zn), 0.5g of benzoyl peroxide, 0.5g of polyethylene glycol dimethacrylate, and 0.25g of triethylene glycol diacrylate were mixed and stirred at room temperature for 12h, filtered, and dripped into the mold drop by drop, reacted at 60°C under a helium atmosphere for 26h. After the reaction, the mold was removed, the lens was placed in pure water for hydration for 10h, and then transferred to standard saline to obtain an anti-blue light hydrogel contact lens.
[0182] Comparative Example 11 Preparation of hydrogel lenses
[0183] 40g of glyceryl methacrylate, 10g of N-vinyl pyrrolidone, 0.5g of benzoyl peroxide, 0.5g of polyethylene glycol dimethacrylate, and 0.25g of triethylene glycol diacrylate were mixed and stirred at room temperature for 12h, filtered, and dripped into a mold drop by drop, reacted at 60°C for 26h under a helium atmosphere, demolded after the reaction, placed in pure water for hydration for 10h, and then transferred to standard saline to prepare a hydrogel contact lens.
[0184] Example 37 Preparation of Anti-Blue Light Hydrogel Lenses
[0185] 46g of hydroxyethyl methacrylate, 4g of methacrylic acid, 0.025g of anti-blue light agent (II-1-Zn), 0.3g of azobisisoheptanonitrile, 0.3g of azobisisobutyronitrile and 0.4g of trimethylolpropane trimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 90°C for 24h under a nitrogen atmosphere. After the reaction, the mold was removed, the lens was placed in pure water for hydration for 12h, and then transferred to standard saline to obtain an anti-blue light hydrogel contact lens.
[0186] Comparative Example 12 Preparation of hydrogel lenses
[0187] 46g of hydroxyethyl methacrylate, 4g of methacrylic acid, 0.3g of azobisisoheptanenitrile, 0.3g of azobisisobutyronitrile and 0.4g of trimethylolpropane trimethacrylate were mixed and stirred at room temperature for 5h, filtered, and dripped into a mold drop by drop, reacted at 90°C for 24h under a nitrogen atmosphere, demolded after the reaction, placed in pure water for hydration for 12h, and then transferred to standard saline to prepare a hydrogel contact lens.
[0188] Example 38 Preparation of Anti-Blue Light Hydrogel Lenses
[0189] 40g of hydroxyethyl methacrylate, 3g of methacrylic acid, 7g of N,N-dimethylacrylamide, 0.05g of anti-blue light agent (compound II-1-Mg), 0.5g of bis(2-phenylethoxy)peroxydicarbonate, 0.25g of triallyl isocyanurate, and 0.25g of divinyl polyethylene glycol were mixed and stirred at room temperature for 8h, filtered, and dripped into a mold drop by drop, reacted at 80°C for 32h under a nitrogen atmosphere, demolded after the reaction, hydrated in a 5% polyethylene glycol 200 aqueous solution for 1h, then placed in pure water for hydration for 6h, and then transferred to standard saline to obtain an anti-blue light hydrogel contact lens.
[0190] Comparative Example 13 Preparation of hydrogel lenses
[0191] 40g of hydroxyethyl methacrylate, 3g of methacrylic acid, 7g of N,N-dimethylacrylamide, 0.5g of bis(2-phenylethoxy)peroxydicarbonate, 0.25g of triallyl isocyanurate, and 0.25g of divinyl polyethylene glycol were mixed and stirred at room temperature for 8h, filtered, and dripped into a mold drop by drop, reacted at 80°C for 32h under a nitrogen atmosphere, demolded after the reaction, hydrated in a 5% polyethylene glycol 200 aqueous solution for 1h, then placed in pure water for hydration for 6h, and then transferred to standard saline to obtain an anti-blue light hydrogel contact lens.
[0192] Example 39 Preparation of hydrogel lenses
[0193] 34 g of hydroxyethyl methacrylate, 16 g of N,N-dimethylacrylamide, 0.0125 g of an anti-blue light agent (compound II-1-Cu), 0.25 g of benzoyl peroxide, 0.1 g of triethylene glycol dimethacrylate, and 0.5 g of polyethylene glycol dimethacrylate were mixed and stirred at room temperature for 16 hours, filtered, and dripped into a mold drop by drop, reacted at 70°C under a nitrogen atmosphere for 24 hours, demolded after the reaction, placed in a 0.01% polyethylene glycol 400 aqueous solution for hydration for 8 hours, hydrated in pure water for 3 hours, and then transferred to standard saline to prepare an anti-blue light hydrogel contact lens.
[0194] Comparative Example 14 Preparation of hydrogel lenses
[0195] 34 g of hydroxyethyl methacrylate, 16 g of N,N-dimethylacrylamide, 0.25 g of benzoyl peroxide, 0.1 g of triethylene glycol dimethacrylate, and 0.5 g of polyethylene glycol dimethacrylate were mixed and stirred at room temperature for 16 hours, filtered, and dripped into a mold drop by drop, reacted at 70°C under a nitrogen atmosphere for 24 hours, demolded after the reaction, placed in a 0.01% polyethylene glycol aqueous solution 400 for hydration for 8 hours, hydrated in pure water for 3 hours, and then transferred to standard saline to prepare an anti-blue light hydrogel contact lens.
[0196] Example 40 Comparison of transmittance of anti-blue light contact lenses
[0197] The contact lens was placed close to the optical glass translucent surface of a cuvette filled with physiological saline (standard saline, refer to GB11417.4-2012), and its transmittance was measured at a wavelength of 380 to 800 nm; the results are shown in Table 1.
[0198] Table 1 Transmittance of anti-blue light contact lenses
[0199]
[0200]
[0201] From the above examples and comparative examples, it can be seen that the anti-blue light lenses of the present invention have strong blocking selectivity for harmful blue light in the blue light transmittance part. The average spectral transmittance of the anti-blue light contact lenses at 385-445nm is less than 80%, and the average spectral transmittance of the more preferred formula at 385-445nm is less than 30%, and the more preferred can be less than 10%; the average spectral transmittance at 446-505nm is higher than 70%, and the average spectral transmittance at 446-505nm of the more preferred formula is higher than 80%, and the more preferred can be higher than 95%. The average spectral transmittance of the hydrogel lenses without adding blue light absorbers at 385-445nm and 446-505nm is higher than 95%; the commercially available lenses will absorb blue light in both the harmful blue light band (385-445nm) and the beneficial blue light band (446-505nm), and the selectivity for absorbing harmful blue light is low.
[0202] Embodiment 41
[0203] Taking Example 28 as an example, three groups of lenses were taken to test their transmittance data in standard saline and placed in sunlight for 36 hours, which was carried out for 6 days (all sunny days), with 6 hours of exposure every day and transmittance tested every two days after exposure. The spectral transmittance of the lenses at 385-445nm before and after illumination was compared to determine the photostability of the lenses.
[0204] Table 2 Transmittance of anti-blue light contact lenses before and after illumination
[0205]
[0206] The spectral transmittance of the lens in the 385-445nm band basically did not change before and after exposure to sunlight, indicating that the anti-blue light lens is relatively stable under light and will not reduce the anti-blue light effect of the lens due to absorption of light.
[0207] Embodiment 42
[0208] The anti-blue light hydrogel lenses of Example 30 were divided into 6 groups. After the transmittance was tested, they were placed in standard saline and stored at constant temperatures of 25°C and 45°C for 9 months (3 groups at each temperature). The lenses were taken out every three months to test the transmittance.
[0209] Table 3 Transmittance of anti-blue light contact lenses before and after storage at different temperatures
[0210]
[0211] When the lenses are stored at 25°C and 45°C, the blue light spectrum transmittance of the lenses in the range of 385-445nm remains basically unchanged, indicating that the anti-blue light effect of the lenses will not be reduced when stored at normal or higher storage temperatures.
[0212] Embodiment 43
[0213] After selecting 3 anti-blue light lenses of Example 27 for transmittance testing, they were placed in an ethanol solution for 6 hours, and then replaced with standard saline at the end of 2 hours, 4 hours, and 6 hours to test the transmittance of the lenses. After the test, the lenses that had been immersed for 2 hours and 4 hours were put back into the ethanol solution and the timing was continued.
[0214] Table 4 Transmittance of anti-blue light contact lenses before and after immersion in ethanol
[0215]
[0216] After the hydrated lens was immersed in ethanol for 2h, 4h, and 6h, the anti-blue light effect of the lens did not change significantly, indicating that the blue light absorber did not precipitate or precipitated less in the organic alcohol solvent.
[0217] Embodiment 44
[0218] The preferred lens example 34 and comparative example 9 were tested for cytotoxicity of the anti-blue light lenses according to the in vitro cytotoxicity test method of GB / T16886.5-2017. Both the lenses with and without anti-blue light agents were non-toxic.
[0219] GB T 16886.5-2017 Biological Evaluation of Medical Devices Part 5: In vitro cytotoxicity test proposes that a quantitative evaluation of cell activity decreases by more than 30% is considered to be cytotoxic. The cell proliferation rates of the lenses of Example 34 and Comparative Example 9 in different concentrations of extracts are all above 70%, and the lenses before and after adding the anti-blue light agent are non-toxic, which means that the addition of the anti-blue light agent has no effect on the cytotoxicity of the lens, which meets the safety evaluation requirements of the lens.
Claims
1. An anti-blue light contact lens, characterized in that: The anti-blue light contact lens comprises at least one reactive monomer, a cross-linking agent, an initiator and an anti-blue light agent which are polymerized by thermal initiation; the structure of the anti-blue light agent is as follows:
2. The anti-blue light contact lens according to claim 1, characterized in that: The anti-blue light contact lens comprises at least one reactive monomer, a cross-linking agent, a solvent, an initiator and an anti-blue light agent and is polymerized by thermal initiation.
3. The anti-blue light contact lens according to claim 2, characterized in that: Calculated by mass, the reaction monomer is 100 parts, the solvent is 0-30% of the reaction monomer mass, the anti-blue light agent accounts for 0.01%-0.5% of the reaction monomer mass; the initiator accounts for 0.01-1.5% of the reaction monomer mass; the cross-linking agent accounts for 0.01-1.5% of the reaction monomer mass.
4. The anti-blue light contact lens according to claim 1 or 2, characterized in that: The reactive monomers include methacrylate monomers, and the methacrylate monomers are present in an amount of 1 to 100 parts.
5. The anti-blue light contact lens according to claim 4, characterized in that: The reactive monomers further include one or more of amide monomers or silicone monomers, wherein the amide monomers account for 0 to 50 parts, and the silicone monomers account for 0 to 55 parts.
6. The anti-blue light contact lens according to claim 4, characterized in that: The methacrylate monomers include any one or more of hydroxyethyl methacrylate, glycidyl methacrylate, glyceryl methacrylate, hydroxybutyl methacrylate, hydroxypropyl methacrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, and isobornyl methacrylate.
7. The anti-blue light contact lens according to claim 5, characterized in that: The amide monomers include any one or more of N-vinyl pyrrolidone, N,N-dimethylacrylamide, and N-methyl-N-vinylacetamide; the silicone monomers include any one or more of 3-(3-methacryloxy-2-hydroxypropyl)propylbis(trimethylsiloxane)methylsilane, 3-acrylamidopropyltris(trimethylsiloxy)silane, monomethacrylamideoxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, methacryloxypropyltris(trimethylsiloxy)silane, monomethacryloxypropyl-terminated mono-n-butyl-terminated polydimethylsiloxane, and fluorinated silicone methacrylate.
8. The anti-blue light contact lens according to claim 1 or 2, characterized in that: The initiator includes any one or two of azobisisobutyronitrile, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, bis(2-phenylethoxy) peroxydicarbonate, benzoyl peroxide, and azobisisoheptylnitrile; the crosslinking agent includes any one or more of divinyl polyethylene glycol ester, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, triallyl isocyanurate, diethylene glycol divinyl ether, polyethylene glycol dimethacrylate, triethylene glycol diacrylate, and trimethylolpropane trimethacrylate.
9. The anti-blue light contact lens according to claim 2, characterized in that: The solvent includes any one or more of dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.
10. The method for preparing the anti-blue light contact lens according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mix the reaction monomer, initiator, cross-linking agent and anti-blue light agent in proportion, stir, filter, and drop into the contact lens mold, initiate polymerization and solidify by heat, hydrate with a hydrating liquid, and then put into standard saline to prepare the anti-blue light contact lens; Alternatively, the reaction monomer, solvent, initiator, crosslinking agent and anti-blue light agent are mixed in proportion, stirred, filtered, and added dropwise to a contact lens mold, thermally initiated polymerization and cured, hydrated with a hydrating liquid, and then placed in standard saline to obtain an anti-blue light contact lens.
11. The method for preparing the anti-blue light contact lens according to claim 9, characterized in that: The thermal polymerization conditions are: reacting at a temperature of 60 to 130° C. for 1 to 40 hours in an inert gas atmosphere, wherein the inert gas includes any one of nitrogen, helium, and argon.
12. The method for preparing the anti-blue light contact lens according to claim 9, characterized in that The hydration liquid includes pure water and an aqueous solution containing a surfactant or an aqueous solution of an organic solvent. The surfactant includes any one or two of poloxamer, polyether silicone oil, polyethylene glycol, and Tween. The organic solvent includes any one or two of ethanol, isopropanol, propylene glycol, glycerol, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide. The hydration time is 2 to 12 hours. The mass fraction of the surfactant in the surfactant aqueous solution is 0.01% to 5% of water. The volume ratio of the organic solvent to water in the organic solvent aqueous solution is 10:90 to 90:10.
Citation Information
Patent Citations
Radiation-proof light-filtering contact lens and production method thereof
CN102382237B
A type of contact lens that protects against ultraviolet light, diffraction light, and blue light.
CN104808355B
Tetraaryl porphyrin compound containing olefine acid ester and application
CN115215874A
Ethylene glycol unit-containing alkenyl-terminated tetraaryl metal porphyrin compound as well as preparation method and application thereof
CN115991709A